Superplastic behavior of 1933 aluminum alloy with bimodal structure at elevated temperatures - Bryukhovetsky, V.V.; Poyda, A.V.; Poyda, V.P.; Milaya, D.E. (Вопросы атомной науки и техники, 2018)
The features of the structural state, phase composition, and deformation relief of the working part of the alloy
1933 specimens are studied. It is determined that the grain-boundary sliding intensively occurs both along the
boundaries of ultra-fine grains and along the boundaries of large polygonized grains parallel to the strain direction of
the specimen. Вивчено особливості структурного стану, фазового складу і деформаційного рельєфу робочої частини
зразків сплаву 1933. Встановлено, що зернограничне проковзування інтенсивно відбувається як по межах
ультратонких зерен, так і по межах великих полігонізованих зерен, паралельних напрямку розтягування
зразка. Изучены особенности структурного состояния, фазового состава и деформационного рельефа рабочей
части образцов сплава 1933. Установлено, что зернограничное проскальзывание интенсивно происходит как
по границам ультратонких зерен, так и по границам крупных полигонизированных зерен, параллельных
направлению растяжения образца.